Volumetric properties of non-aqueous binary mixture of diethanolamine (DEA) and dimethylformamide (DMF). Issue 5 (October 2018) - Murshid, Ghulam; Ghaedi, Hosein; Ayoub, Muhammad; Mjalli, Farouq Sabri; Garg, Sahil
Highlights: Measuring volumetric properties of non-aqueous system of (DEA + DMF). To analyze the effect of temperature and concentration on the properties using RSM. Significant effect of temperature and concentration on the properties. Using JAM as accurate model to correlate the volumetric properties data. Abstract: This paper reports the volumetric properties such as density, molar volume and isobaric thermal expansion of non-aqueous system of DMF-DEA. The values of volumetric properties were reported for several mole fractions of DMF ( x 1 ) and DEA ( x 2 ) and temperature from 298.15 to 343.15 K. In order to investigate the significance of temperature and concentration on the each volumetric property and develop regression models, a user-defined method of response surface methodology (RSM) was applied. A predictive equation called Jouyban-Acree model (JAM) was used to predict the volumetric properties of the binary mixture. The accuracy and capability of JAM were compared with regression model. The results revealed that JAM is capable of correlating volumetric properties very well and is an accurate model for prediction of the volumetric properties of the binary mixture. The analysis of variance (ANOVA) results showed that temperature and concentration are highly significant and have the strong influence on the volumetric properties. The investigation of experimental data shows that the density and molar volume values increase with rising in the concentration of DEA in the mixture, while isobaric thermal expansion values decrease. Moreover, there was an increasing trend on the values of molar volume and isobaric thermal expansion as the temperature increased, whereas the density of binary mixture decreased with an increase in temperature.